Arah Pengembangan Transportasi Perkotaan di Indonesia - Willy Tumewu (The Institute for Research and Community Services, Institut Teknologi Bandung, 1997)
The larger cities of Indonesia already suffer from traffic congestion while the economic development is still low compared to developed countries. The development of industries will trigger urbanization and increase the income per capita, which will almost certainly increase the mobility and motorisation of the society. This paper describes an attempt to make a global comparison about urban transportation, and proposes development directions which rely on public and mass transportation, with a dense network of not too wide roads. For this purpose the urban population density has to be maintained at a high level, and experiments and research are needed to find a best pattern, as soon as possible. This type of urban development is expected to be gasoline efficient, with a high level of traffic safety.